Kinematic characteristics of high step frequency sprinters and long step length sprinters at top speed phase - Toyoshima, R.; Sakurai, S. (International Journal of Sport & Health Science, 2016)
The present study aimed to clarify kinematics among sprinters with similar step length but different step frequencies, and with similar step frequencies but different step lengths in sprinting. We collected kinematic data from 54 sprinters at approximately the 60 m point of a 100-m sprint using a high-speed camera. The sprinters within 0.5SD from the mean value of each of step frequency and length at top speed phase were included in the `SL-similar` (n=22, step frequency: 3.99-5.19 Hz, step length: 2.07-2.15 m) and the `SF-similar` (n=22, step frequency: 4.51-4.72 Hz, step length: 1.93-2.33 m) groups, respectively. In the SL-similar group, higher step frequency was correlated with shorter stance time (r=-0.899), and a more vertical thigh angle at take-off (r=0.623). In the SF-similar group, longer step length was correlated with greater distance of the hip during flight phase (r=0.847), and a larger vertical acceleration of the forward swinging leg relative to the hip (r=0.438). In conclusion, leg kinematics at touchdown and take-off are important for high step frequency in similar step length, and forward swinging leg kinematics are important for long step length in similar step frequency.